Implementasi Augmented Reality Berbasis Android dalam Pengenalan Rumah Adat Sulawesi Tenggara - Yanita, Putri Apri; Mardiawati, Mardiawati; Fakhrunnisaa, Nur (JISTech : Journal of Information Systems and Technology, 2025)
The conservation of indigenous culture, particularly the traditional dwellings of Southeast Sulawesi, encounters obstacles owing to technological progress and changing preferences among younger demographics. This study created a Augmented Reality (AR) application for presenting traditional dwellings of Southeast Sulawesi utilizing the Multimedia Development Life Cycle (MDLC) methodology. This program enables users to obtain information regarding traditional houses via interactive 3D models, supplemented by text and voice, employing marker-based tracking technology. Testing was performed via Black Box Testing and User Acceptance Testing (UAT), which demonstrated that the application operates optimally on devices with a minimum of 3GB of RAM. User evaluation findings revealed a satisfaction level of 81.27%, classified as "Very Easy to Use." This program possesses the potential to serve as an innovative solution for cultural education and to augment tourism appeal via a contemporary digital approach. Anticipated advancements will encompass performance optimization and the incorporation of interactive features to improve user experience